2015
DOI: 10.1186/1471-2156-16-s1-s1
|View full text |Cite
|
Sign up to set email alerts
|

Candidate genes in quantitative trait loci associated with absolute and relative kidney weight in rats with Inherited Stress Induced Arterial Hypertension

Abstract: BackgroundThe kidney mass is significantly increased in hypertensive ISIAH rats with Inherited Stress Induced Arterial Hypertension as compared with normotensive WAG rats. The QTL/microarray approach was carried out to determine the positional candidate genes in the QTL for absolute and relative kidney weight.ResultsSeveral known and predicted genes differentially expressed in ISIAH and WAG kidney were mapped to genetic loci associated with the absolute and relative kidney weight in 6-month old F2 hybrid (ISIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…They demonstrated that high glucose could induce apoptosis through increased ROS in cardiac microvascular endothelial cells. Oxidative stress has been shown to induce caspase-dependent apoptotic genes and inhibit metabolic gene expression (32,33). These results are consistent with previous reports from other investigators.…”
Section: Discussionsupporting
confidence: 93%
“…They demonstrated that high glucose could induce apoptosis through increased ROS in cardiac microvascular endothelial cells. Oxidative stress has been shown to induce caspase-dependent apoptotic genes and inhibit metabolic gene expression (32,33). These results are consistent with previous reports from other investigators.…”
Section: Discussionsupporting
confidence: 93%
“…Genetics models as well as computational genomics were presented at the conference from the beginning and highlighted at BioMed Central special journal issues since 2014 ( https://bmcgenomics.biomedcentral.com/articles/supplements/volume-15-supplement-12 ) [ 1 3 ]. It also included BMC Genetics Supplement ( https://bmcgenet.biomedcentral.com/articles/supplements/volume-16-supplement-1 ) [ 4 ], selected papers in microbiology models ( https://bmcmicrobiol.biomedcentral.com/articles/supplements/volume-16-supplement-1 ), structural biology ( https://bmcstructbiol.biomedcentral.com/articles/supplements/volume-18-supplement-1 ). To accompany this Special Issue, other Supplements compiling selected BGRS-2018 articles in the fields of genomics, bioinformatics, plant biology, evolutionary biology and systems biology are published as a part of following journal series: BMC Genomics, BMC Bioinformatics, BMC Systems Biology, BMC Medical Genomics, BMC Evolutionary Biology and BMC Plant Biology [ 5 – 9 ].…”
mentioning
confidence: 99%
“…The Belyaev Conference-2017 (“Belyaev Readings - 2017”) was devoted to science legacy of outstanding scientist, evolutionist and geneticist, full member of the USSR Academy of Sciences, Professor Dmitry K. Belyaev (1917–1985) to mark the 100-th anniversary since his birth [ 16 ]. Such science problems include selection works on fox and rat lines [ 17 ], search for genes related to climate adaptation [ 18 ] including published earlier at BMC Genetics [ 4 ].…”
mentioning
confidence: 99%
“…Previously published special issues of BMC Genetics, BMC Genomics and BMC Evolutionary Biology covered the proceeding of BGRS\SB-2016 conference and SBB-2015 School in Novosibirsk [ 1 – 5 ] as well as BGRS\SB-2014 event ( https://bmcgenomics.biomedcentral.com/articles/supplements/volume-15-supplement-12 ). First BMC Genetics special issue paper in the area of genetics was presented at the BGRS\SB-2014 conference series in Novosibirsk [ 6 ].…”
mentioning
confidence: 99%